Exergaming as Part of the Telerehabilitation Can Be Adequate to the Outpatient Training: Preliminary Findings of a Non-randomized Pilot Study in Parkinson's Disease - Cikajlo, Imre; Hukić, Alma; Zajc, Dejana (Frontiers in Neurology, 2021)
Parkinson's disease is a long-term and progressive degenerative disorder of the nervous system, affecting primarily motor coordination, noticeable as a tremor in one hand. Recent studies reported on positive outcomes of intensive physiotherapy of upper extremities. We built a telerehabilitation system with virtual pick and place tasks for small scale hand movements, and designed a pilot study to find whether such exergaming as a telerehabilitation service provides comparable outcomes as an outpatient exergaming service. A non-randomized pilot trial was designed. Hospital outpatients (28/40) with Parkinson's disease were recruited. Those meeting the inclusion criteria were divided into two groups; seven outpatients were assigned to the home (H) group and 21 outpatients to the hospital (URI) group. Both groups received 10 days of exergaming over the course of 2 weeks, each daily session lasting a maximum of 1 h. Primary outcomes were clinical tests; Box and Blocks Test (BBT), Jebsen Hand Function Test (JHFT), and Unified Parkinson's Disease Rating Scale (UPDRS part III) were carried out before and after the study. Secondary outcomes were hand kinematics and exergaming results; number of successfully moved objects and task time. Statistical analysis was carried out to find significant (p < 0.05) differences and Cohen's U3 was used to determine effect sizes. The differences between the groups in gender (p = 0.781), age (p = 0.192), and duration of the disease (p = 0.195) were tested with Bartlett's test and no statistical differences were found with an F test. Both groups demonstrated statistically significant improvements in clinical test UDPRS III (p = 0.006 and p = 0.011) and the hospital group also in BBT (p = 0.002) and JHFT (p = 0.015) and with UDPRS III and JHFT even in favor of the home group (χ2 = 5.08, p = 0.024, χ2 = 7.76, p = 0.005). Nevertheless, the exergaming results show significant improvement after training (U3 > 0.86). Exergaming has already been suggested as an effective approach in the planning of rehabilitation tasks for persons with Parkinson's disease. We have prepared a pilot study demonstrating that exergaming at home with telerehabilitation support may provide comparable clinical outcomes. The study shall be followed by a randomized study with higher statistical power to provide clinical evidence. Nevertheless, carrying out even part of the rehabilitation program at home is crucial for the development of future telerehabilition clinical services. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03175107.